Peningkatan Pemahaman Iman dan Implementasi Nilai Kristiani melalui Project-Based Learning pada Siswa Kelas 10 di Tanjung Palas Barat - Sherli Sherli; Gregorius Daru Wijoyoko (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
Catholic Religious and Character Education (PAK-BP) aims to form students’ character based on Christian values; however, its implementation in schools often remains theoretical. This classroom action research (CAR) seeks to enhance students’ understanding of faith and the application of Christian moral values through the Project-Based Learning (PJBL) method. PJBL emphasizes contextual and experiential learning through projects relevant to students’ daily lives. The research subjects were Grade 10 students in Tanjung Palas Barat, with instruments including classroom observations, project rubrics, and written reflections. The findings show that the use of PJBL effectively improved students’ understanding of faith and their ability to apply Christian moral values in various social, environmental, and school projects. These projects included community service, environmental stewardship, and faith-based school activities that fostered collaboration, responsibility, and compassion. The outcomes also align with Church teachings as stated in the Catechism of the Catholic Church (nos. 1700–1789) and Amoris Laetitia, emphasizing moral formation and faith lived through love. In conclusion, the implementation of PJBL in Catholic Religious Education successfully internalized Christian values in a contextual and meaningful way. This method enables students not only to learn about faith but also to practice it through real-life actions rooted in Gospel values.